Hubungan Motivasi Kerja dengan Displin Kerja Karyawan di PT.Perkebunan Nusantara III (Persero) Unit Kebun Bandar Selamat - Fitri Syahdani Ningsih Lubis; Azhar Aziz (Jouska: Jurnal Ilmiah Psikologi, 2023)
This study aims to see the relationship between work motivation and work discipline of employees at PT. Perkebunan Nusantara III (Persero) Unit Kebun Bandar Selamat. The population of this study were all 187 employees, and the sample in this study amounted to 47 people. The sampling technique used was perposive sampling. This research method uses quantitative methods. Data collection uses a work motivation scale and a work discipline scale which is measured using a Likert scale. The data analysis technique uses the Product Moment Correlation technique. The results showed a significant correlation value of p = 0.000 0.05, meaning that there was a positive relationship between work motivation and work discipline of employees at PT. Perkebunan Nusantara III (Persero) Unit Kebun Bandar Selamat, with a determinant coefficient (r2) of 0.586 or 58, 6%. In other words, the hypothesis is accepted. Work discipline is classified as high (empirical mean = 102.55 hypothetical mean = 82.5 where the difference is more than SD = 5.445), and for work motivation it is high (empirical mean = 107.04 hypothetical mean = 90 where the difference is more than SD = 6.934).